Problems Faced by Iraqi Teachers of English in Teaching Iraq Opportunities Textbook at Primary Schools - Hayfaa Kadhim Mohammed misanjas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
This study aims at identifying and classifying the  problems in teaching Iraq opportunities textbook for Iraqi teachers .The   population   of   this   study   comprises  the   teachers  of  English  at  the  primary   stages   in  General   Directorate   of   Education   in   Misan   Governorate .  forty   teachers    are  randomly  assigned  as  the  main  sample  , while   ten  teachers   are  randomly  assigned  as  the   pilot  sample .In  order  to  achieve  the  aims  of  this  study  and  to  point  out  the  problems  that  faced  by  Iraqi  teachers  when  teaching  Iraq  Opportunities  textbook  .     At  first ,  the  researcher  has  constructed  an  open  questionnaire  contained  the  following  open  questions : " Do  you  have  any  problems  in  teaching " Iraq  Opportunities " textbook "  and " What  are  the  mean  problems  that  you  face  in  teaching "  Iraq  Opportunities  "  textbook "                                                   The obtained results of this study show that indicates  that   the   average   weighted   mean  of  this  area   is  (2.17)   which   is   higher   than   the   theoretical   mean  which  means  ( 2 ) .  This   means  that  the  teachers  efficiency  in  this  area  is  active  since  the  items  of  this  area  with   numbers  7 , 1 , 3 , 5  and  10  have  the  weighted  means  of  ( 2.99 ,  2.75 ,  2.45 , 2.35 and  2.3 )  .  Nevertheless  , items  with  numbers  (  6 , 2  , 4 , 9  and  8 )  have   the   weighted    means   of     ( 1.99  ,  1.98  ,  1.8 , 1.8  and  1.3 )  respectively  ,  which   are   less   than   the   theoretical    mean   ( 2 ) .  This   means  that  these  items  are  more  problematic   in   this  area .   Therefore  ,  it  concludes   that  this   area  which  is  related  to   the  teacher  efficiency  is  acceptable   because  the  average  weighted  mean  is  ( 2.17 )  which  is  more  than  the theoretical mean which is (2)